Semen Quality of Sentul Cock with Different Immunoglobulin Yolk Concentrations - Ria Ariyanti; Niken Ulupi; Tuti Suryati; Raden Iis Arifiantini (Buletin Peternakan, 2019)
The aim of this study was to evaluate the effect of different IgY concentrations on the quality of semen (macroscopic and microscopic) and testicular morphometry (weight, length and width of the testes) of Sentul cock testis and its ability to fertilize hens. This study used 4 months of 20 Sentul cocks consisting 10 high IgY concentration cocks and low IgY concentration cocks. This study used a complete randomized design (RAL) with 2 treatments namely low and high IgY concentration and10 times repetitions. Data were analyzed using t-test minitab program versions 16. Based on the result, different IgY concentrations did not affect the quality of semen and testicular morphometrics, but high IgY concentration cocks were able to fertilize more hens than the low IgY concentrations one by using dilution methods. This proves that high IgY concentration cocks are more effective and efficient cocks or stud.